The relationship between WIG-subindexes: evidence from the Warsaw Stock Exchange - Gurgul, Henryk; Syrek, Robert (Managerial Economics, 2015)
Evidence on links among the major Warsaw Stock Exchange subindexes using daily data from the period of 2011.03.01 to 2014.07.21 is provided in the paper. The empirical study for eleven WIG-sectoral subindexes with 844 observations was conducted by means of Regular Vine Copulas. The application of these copulas allowed us to identify the pairwise structure of the dependence of subindexes under study. The results conﬁrm the leading role of the banking sector in the Polish economy. The dependence structure of the WIG-banking subindex and other subindexes is, in general, asymmetrical. The links between returns of the subindexes are more pronounced in the left tails; i.e., in the bear phase of ﬁnancial markets. This study suggests the usefulness of Regular Vine Copulas in analyzing dependence structures of a number of ﬁnancial time series.